Regulation of Alloantibody Responses - Chong, Anita S.; Sage, Peter T.; Alegre, Maria-Luisa (Frontiers in Cell and Developmental Biology, 2021)
The control of alloimmunity is essential to the success of organ transplantation. Upon alloantigen encounter, naïve alloreactive T cells not only differentiate into effector cells that can reject the graft, but also into T follicular helper (Tfh) cells that promote the differentiation of alloreactive B cells that produce donor-specific antibodies (DSA). B cells can exacerbate the rejection process through antibody effector functions and/or B cell antigen-presenting functions. These responses can be limited by immune suppressive mechanisms mediated by T regulatory (Treg) cells, T follicular regulatory (Tfr) cells, B regulatory (Breg) cells and a newly described tolerance-induced B (TIB) cell population that has the ability to suppress de novo B cells in an antigen-specific manner. Transplantation tolerance following costimulation blockade has revealed mechanisms of tolerance that control alloreactive T cells through intrinsic and extrinsic mechanisms, but also inhibit alloreactive B cells. Thus, the control of both arms of adaptive immunity might result in more robust tolerance, one that may withstand more severe inflammatory challenges. Here, we review new findings on the control of B cells and alloantibody production in the context of transplant rejection and tolerance.